The Interactome in the Evolution From Frailty to Sarcopenic Dependence - Coto-Montes, Ana; González-Blanco, Laura; Antuña, Eduardo; Menéndez-Valle, Iván; Bermejo-Millo, Juan Carlos; Caballero, Beatriz; Vega-Naredo, Ignacio; Potes, Yaiza (Frontiers in Cell and Developmental Biology, 2021)
Biomarkers are essential tools for accurate diagnosis and effective prevention, but their validation is a pending challenge that limits their usefulness, even more so with constructs as complex as frailty. Sarcopenia shares multiple mechanisms with frailty which makes it a strong candidate to provide robust frailty biomarkers. Based on this premise, we studied the temporal evolution of cellular interactome in frailty, from independent patients to dependent ones. Overweight is a recognized cause of frailty in aging, so we studied the altered mechanisms in overweight independent elderly and evaluated their aggravation in dependent elderly. This evidence of the evolution of previously altered mechanisms would significantly support their role as real biomarkers of frailty. The results showed a preponderant role of autophagy in interactome control at both different functional points, modulating other essential mechanisms in the cell, such as mitochondrial capacity or oxidative stress. Thus, the overweight provoked in the muscle of the elderly an overload of autophagy that kept cell survival in apparently healthy individuals. This excessive and permanent autophagic effort did not seem to be able to be maintained over time. Indeed, in dependent elderly, the muscle showed a total autophagic inactivity, with devastating effects on the survival of the cell, which showed clear signs of apoptosis and reduced functional capacity. The frail elderly are in a situation of weakness that is a precursor of dependence that can still be prevented if detection is early. Hence biomarkers are essential in this context.